Amphiphilic polypyridyl ruthenium complexes: synthesis, characterization and aggregation studies - Bhand, Sujit; Lande, Dipali N.; Pereira, Eulalia; Gejji, Shridhar P.; Weyhermueller, Thomas; Chakravarty, Debamitra; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Polyhedron, 2019)
{Synthesis and characterization of five amphiphilic ruthenium(11) complexes of the type [Ru(Cn)(3)]center dot(PF6)(2) (Cn = 4,4'-dialkyl-2,2'-bipyridine
Keywords: 2; 2 `-bipyridine; Aggregation; Amphiphilic ligand; Metallosurfactant; Ruthenium complexes

Synthesis and biological activity of imidazole based 1,4-naphthoquinones - Choudhari, Dinkar; Salunke-Gawali, Sunita; Chakravarty, Debamitra; Shaikh, Samir R.; Lande, Dipali N.; Gejji, Shridhar P.; Rao, Pradeep Kumar; Satpute, Surekha; Puranik, Vedavati G.; Gonnade, Rajesh (New Journal of Chemistry, 2020)
Design and development of drugs in multi-drug resistant (MDR) infections have been of growing interest. We report the syntheses, and antibacterial and antifungal activities of imidazole-based 1,4-naphthoquinones (I-1 to I-4; 1-alkyl-2-methyl-1H-naphtho[2,3-d]imidazole-4,9-dione (alkyl = methyl to butyl)) and their precursors (B-3; N-(3-chloro-1,-dioxo-1,4-dihydronaphthalen-2-yl)acetamide) and A-1 to A-4; N-(3-(alkylamino)-1,4-dioxo-1,4-dihydronaphthalen-2-yl)acetamide (alkyl = methyl to butyl). Crystal structures of B-3, A-1 to A-3 and I-2 to I-4 were obtained through single crystal X-ray diffraction experiments. Electronic structure and charge distribution have further been characterized with the use of Density Functional Theory. Seven of these derivatives display a broad spectrum of antibacterial activity against few selected bacterial strains (Gram-positive and Gram-negative). As demonstrated MIC values with B-2 and B-3 against bacterial isolates were 8-64 mu g ml(-1) and those against pathogenic yeast, C. albicans, were observed in the range of 128-256 mu g ml(-1). MIC data of these derivatives suggest them to be promising against pathogens.

Reactions of 2,3-dibromonaphthalene-1,4-dione and pyridyl amines: X-ray structures, DFT investigations, and selective detection of the Hg2+ and Ni2+ ions - Aggrwal, Gunjan; Salunke-Gawali, Sunita; Gejji, Shridhar P.; Nikalje, Milind; Chakravarty, Debamitra; Verma, Prakash L.; Gosavi-Mirkute, Prajkta; Harihar, Shital; Jadhav , Mahesh; Puranik, Vedavati G. (Engineered Science, 2021)
<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">In this work, the products formed by the reaction between 2,3-dibromonaphthalene-1,4-dione with (pyridine-2-yl)methanamine and (pyridine-4-yl)methanamine are discussed in detial. The products 2-amino-3-bromonaphthalene-1,4-dione (<span style="font-weight: 700; color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; background-color: rgb(217, 217, 217);">A<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">) and 2-aminonaphthalene-1,4-dione (<span style="font-weight: 700; color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; background-color: rgb(217, 217, 217);">B(1)<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">) obtained are characterized through 1H and 13C-NMR, FTIR, mass spectrometry, single-crystal X-ray diffraction experiments, which are in conjunction with wB97X based density functional theory. <span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">compound <span style="font-weight: 700; color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; background-color: rgb(217, 217, 217);">A<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);"> can effectively and selectively detect Hg2+ and Ni2+ ions, and proposes a potential mechanism of action<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">.